GII.4 human norovirus and G8P[1] bovine-like rotavirus in oysters (Crassostrea gigas) from Argentina - Mozgovoj, Marina Valeria (2022)
Bivalve mollusks have been widely recognized as an important source of foodborne virus. The aim of this work was to determine the presence of norovirus (NoV) and rotavirus (RVA) in Pacific cupped oyster (Crassostrea gigas) from Buenos Aires, Argentina. A total of 88 oyster were processed. 7% of pooled samples resulted positive for NoV GII by RT-qPCR. The nucleotide analysis showed that it was closely related to GII.4/Sydney. Regarding RVA, 21% were positive by RT-qPCR targeting the NSP3 gene. RVA from one pool was isolated in cell culture and infective viral particles were evidenced by immunofluorescence. The genotype constellation of RVA/Oyster-wt/Crassostrea gigas_BA/2015/G8P[1] isolated strain was G8-P[1]-I2-R2-C2-M2-A3-N2-T6-E2-H3, which has a bovine-like genome backbone. Notably, RVA possesses an E2 genotype which is different from the characteristic E12 genotype of RVA circulating in animal species from South America. Our findings evidence not only the presence of enteric viruses in oysters from Argentina, but most important the viability of RVA. This result pose the need to implement surveillance programs to prevent potential foodborne viral outbreaks due to the consumption of contaminated shellfish. Resumen: Los moluscos bivalvos han sido ampliamente reconocidos como una fuente importante de virus transmitidos por los alimentos. El objetivo de este trabajo fue determinar la presencia de norovirus (NoV) y rotavirus (RVA) en ostras del Pacífico (Crassostrea gigas) de Buenos Aires, Argentina. Se procesaron un total de 88 ostras. El 7 % de las muestras agrupadas dieron positivo para NoV GII mediante RT-qPCR. El análisis de nucleótidos mostró que estaba estrechamente relacionado con GII.4/Sydney. En cuanto a RVA, el 21% dieron positivo por RT-qPCR dirigida al gen NSP3. El RVA de un grupo se aisló en cultivo celular y las partículas virales infecciosas se evidenciaron mediante inmunofluorescencia. La constelación de genotipos de la cepa aislada RVA/Oyster-wt/Crassostrea gigas_BA/2015/G8P[1] fue G8-P[1]-I2-R2-C2-M2-A3-N2-T6-E2-H3, que tiene una Esqueleto del genoma de tipo bovino. En particular, RVA posee un genotipo E2 que es diferente del genotipo E12 característico de RVA que circula en especies animales de América del Sur. Nuestros hallazgos evidencian no solo la presencia de virus entéricos en ostras de Argentina, sino lo más importante, la viabilidad de RVA. Este resultado planteó la necesidad de implementar programas de vigilancia para prevenir posibles brotes virales transmitidos por alimentos debido al consumo de mariscos contaminados.